2008 Triennial Surveillance Review : Background Information and Statistical Appendix. (Policy Papers; Policy Paper ;, 2008)
Country surveillance constitutes an essential part of the IMF's mandate to oversee the international monetary system and to monitor the economic and financial policies of its 185 member countries. The IMF's Executive Board conducts regularly scheduled reviews of country surveillance (the Triennial Surveillance Review) to consider ways to improve its effectiveness. The 2008 review is the first such review since the Executive Board approved, in June 2007, a new Decision on Bilateral Surveillance. This Decision affirms that the focus of bilateral surveillance is on those policies of members that can significantly influence present or prospective external stability. The review focused on the implementation of country surveillance in the recent past, as presented in the following set of papers: -- The overview paper presents the main findings and priority areas for further work. The review finds that stakeholders hold the quality of IMF surveillance in high regard, but that improvements should focus on risk assessment, integration of macroeconomic and financial sector surveillance, multilateral perspectives (cross-border spillovers and cross-country analysis), and exchange rate assessments. The priority areas identified in the review served as key background for the preparation of the IMF's Statement of Surveillance Priorities (SSP). -- The Thematic Findings (Supplement 1) provides supporting analysis on the implementation of bilateral surveillance in the recent past and, particularly, on the appropriateness of its focus and its analytical value added in particular areas, including the overall 'health check', exchange rates, financial sector issues, cross-country analysis and cross-border spillover analysis (including a case study of surveillance in the run up to the subprime crisis), the degree of candor and evenhandedness in surveillance, and the effectiveness of its communication. -- The Background Information paper (Supplement 2) provides further information, including a description of review methodologies, and results including interview findings, surveys of various audiences, and supporting data on the quality of consultation documents. -- The External Consultant's Report provides an independent view of IMF surveillance in Europe.